ANALYSIS OF RESISTANCE OF CASSAVA TAPE BY EXPOSURE TO 1000 Î¼T INTENSITY ELF MAGNETS - Arissofiyah, Akhlaqul; Rusdiana, Desi; Yushardi, Yushardi; Anggraeni, Firdha Kusuma Ayu; Meilina, Ike Lusi; Cahyani, Vandaria Dewi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
Extremely Low Frequency (ELF) electromagnetic waves are electromagnetic waves with a frequency range of 0 to 300 Hz. ELF electromagnetic wave radiation produces non-thermal effects on the biological objects used, meaning that it does not cause temperature changes when interacting with or inducing the system. Electromagnetic waves are waves that arise due to changes in electric fields and strong magnetic fields. This research aims to prove the effect of Extremely low frequency (ELF) magnetic field on the food resilience process. The research method used is experimental research method. This research was carried out in the basic physics laboratory at the University of Jember. Data collection techniques using observation. Based on the research, it can be concluded that ELF magnetic field radiation has the potential as an alternative method in increasing the nutritional value and durability of fermented food ingredients. Exposure to Extremely Low Frequency magnets with an intensity of 1000 Î¼T for 45 minutes resulted in changes in pH value and physical quality that affect food durability in cassava tape.